Can there be a Future Withought a Hero? The Post-socialist Key to Victimisation - Potkonjak, Sanja (2008)
The paper aims at exploring how the socialist past became an esthetical issue, as well as political issue in the construction of the post-socialist Croatian identity. Through the analysis of three art projects staged in Croatia from 2000 to 2008, the paper explores temporality and the arbitrariness of the major narratives that have been shaping identity after 90’ s such as antifascism, victimhood, and newly gained national sovereignty. The goal of the paper is to shed light on how modes of victimhood operate in post-Yugoslav society. Moreover, the paper tries to look into details on how victimhood, and its effects are established in regard to the major lack of dispassionate “ cross-referentiality” when fatality and atrocities are at stake. The enactment of the idea of victimhood is analyzed through the public/political and individual/artistic actions and this allows me to imply that the victimhood (i.e. art and rituals established over it) has been used as a tangible national unifier.